Recovery of citric acid from Citrus peels: ultrasound-assisted extraction optimized by response surface methodology - Fernandes, Filipa Alexandra (2011)
The production of citrus juice generates a large quantity of by-products, which are often discarded or used for animal feed. However, several studies have shown its richness in valuable compounds, namely organic acids. Thus, this work intended to valorize orange and lime peels as renewable sources of citric acid. An experimental design combining five levels of the independent variables time (2–45 min), ultrasonic power (50–500 W), and ethanol proportion (0–100%) was implemented and response surface methodology (RSM) was applied to optimize the extraction process. The UPLC-PDA analysis showed that orange peel presented a higher citric acid content than lime. For lime and orange peels, the extraction yield was maximized by sonicating at low power for 5.8 or 35.5 min, using a low ethanol proportion or only water as a solvent, respectively. Overall, optimal UAE conditions were defined for the sustainable extraction of citric acid from citrus by-products, thus contributing to its valorization and upcycling into natural food ingredients.